1978
DOI: 10.1073/pnas.75.10.5226
|View full text |Cite
|
Sign up to set email alerts
|

Growth cone formation in cultures of sensory neurons.

Abstract: Three experimental situations have been found in which cultured sensory neurons from embryonic chicken will form growth cones from positions along the length of the neurite. If the neurons are dissected with a remaining short axonal stump and plated into serum-free medium, they can form a morphologically normal growth cone from the stump within 15 min, even in the presence of cycloheximide or puromycin. When neurites growing in culture media with low levels of serum are cut at any point with microneedles, grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
1

Year Published

1982
1982
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(85 citation statements)
references
References 26 publications
(22 reference statements)
6
78
1
Order By: Relevance
“…Because microtubules are known to play an essential role in dendritic stability (Bray et al, 1978;Dehmelt et al, 2003;Henley and Poo, 2004;Suter et al, 2004), these results nicely correlate to the observed behavior of developing dendrites in our recordings. They are also consistent with previous reports suggesting that microtubules drive growth cone steering (Suter et al, 2004) and the forward momentum of newly formed protrusions (Baas and Ahmad, 2001).…”
Section: Discussionsupporting
confidence: 74%
“…Because microtubules are known to play an essential role in dendritic stability (Bray et al, 1978;Dehmelt et al, 2003;Henley and Poo, 2004;Suter et al, 2004), these results nicely correlate to the observed behavior of developing dendrites in our recordings. They are also consistent with previous reports suggesting that microtubules drive growth cone steering (Suter et al, 2004) and the forward momentum of newly formed protrusions (Baas and Ahmad, 2001).…”
Section: Discussionsupporting
confidence: 74%
“…4, 9; see also Joshi et al, 1986). Microtubule discontinuity may lead to a local accumulation of membranous vesicles (Bray et al, 1978), thus providing an abundant source of membrane for the rapidly extending growth cone. Such vesicle accumulation was observed in several experiments (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Axonal transection is followed, in many cases, by a process in which the tip of the severed axon is transformed into a motile growth cone (Shaw and Bray, 1977;Bray et al, 1978;Wessells et al, 1978;Baas and Heidemann, 1986;Baas et al, 1987;Rehder et al, 1992;Benbassat and Spira, 1993;Ashery et al, 1996). This growth cone serves as a path-finding sensor, a cytoskeleton assembly apparatus, and a site for membrane insertion (for review, see Letourneau et al, 1992).…”
Section: Abstract: Growth Cone Formation; Axotomy; Calcium; Fura-2; mentioning
confidence: 99%
“…A number of observations that were made in neuronal and other systems support this hypothesis. Low doses of antimicrotubular agents induced growth cone formation in cultured neurons (Bray et al, 1978) and locomotor activity in fibroblasts (Vasiliev et al, 1970(Vasiliev et al, , 1971. Antimicrotubular agents also modulated the rate of intact motor axon sprouting in partially denervated muscles (Hoffman, 1952); low doses of cryptopleurine accelerated sprouting, whereas high doses retarded it.…”
Section: Supernumerary Innervation Produced By Low Doses Of Colchicinementioning
confidence: 99%
“…The ability of colchicine to induce neurite outgrowth, of axons that were separated from their cell bodies to elongate, and of synapses to form rapidly was described previously. A low dose of colchicine initiated growth cone formation in cultured neurons (Bray et al, 1978) and sprouting and synapse formation in the rat dentate gyrus (Goldowitz and Cotman, 1980). Axons that were separated from their cell bodies and grew before undergoing subsequent degeneration were observed in chick brain, spinal cord, and dorsal root ganglia cultures (Levi and Meyer, 1945;Hughes, 1953;Shaw and Bray, 1977).…”
Section: Supernumerary Innervation Produced By Low Doses Of Colchicinementioning
confidence: 99%